Tensile Performance of Inter-Module Connections for Modular Steel Buildings Using Finite Element Method - Shoifah, Umi Arifatus; Husin, Nur Ahmad; Tajunnisa, Yuyun (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Steel modular construction is an innovative technology that uses prefabricated volumetric module units manufactured in a factory and assembled on site via inter-module connections. However, this system's application in high-rise buildings is limited because the structural performance is strongly influenced by the inter-module connection mechanism. This technology uses a translational spring model to transfer loads between modules through inter-module connections. This approach uses threaded steel rod components, connection plates, shear keys, shear plates, and tie plates. This research aims to determine the maximum tensile capacity of the connection. It also aims to study stress distribution due to tensile forces and failure modes in vertical modular connections. This research uses the finite element method (FEM) to perform numerical analysis by applying monotonic loads. Simulation results indicate that the connection's maximum tensile capacity is 307.48 kN, distributed among two rods with capacities of 153.74 kN each at a displacement of 23.2 mm. The rod undergoes elastic deformation up to Fy = 900 MPa, followed by a plastic phase up to nearly Fu = 1,100 MPa, causing permanent strain and necking. Tensile failure occurred due to plasticity and necking conditions.